1991
DOI: 10.1007/bf00685159
|View full text |Cite
|
Sign up to set email alerts
|

Aminoglutethimide in advanced breast cancer: plasma levels and clinical results after low and high doses

Abstract: Drug plasma levels, metabolism data and clinical results were evaluated after the daily administration of either 500 or 1,000 mg aminoglutethimide (AG, Orimeten, Ciba-Geigy) plus hydrocortisone acetate (20 mg b. i. d.). A total of 34 patients with advanced breast cancer entered the study: 17 were given 1,000 mg/day and 17 received 500 mg/day for at least 3 months. A novel HPLC method was developed to determine the levels of AG and its known metabolites [N-acetyl-AG (NAG), formyl-AG, nitroglutethimide, hydroxy-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…AG acts by inhibition of P450 scc and aromatase activity with an IC 50 of 16-40 µM (Vanden Bossche 1992). The plasma levels in patients treated with 1000 mg AG/day reach 70 µmol/l (Strocchi et al 1991). In our system, AG in concentrations of 300 µM did not significantly influence cell viability and cell number, thus arguing against a toxic effect of this compound.…”
Section: Discussionmentioning
confidence: 49%
“…AG acts by inhibition of P450 scc and aromatase activity with an IC 50 of 16-40 µM (Vanden Bossche 1992). The plasma levels in patients treated with 1000 mg AG/day reach 70 µmol/l (Strocchi et al 1991). In our system, AG in concentrations of 300 µM did not significantly influence cell viability and cell number, thus arguing against a toxic effect of this compound.…”
Section: Discussionmentioning
confidence: 49%
“…In this context it is important to note that all drugs used in our experiments were effective within the ‘therapeutic range’ for humans. In patients receiving 1000 mg AG or 1000 mg MTP, respectively, plasma levels of either compound reach 70 μM [31–33]. However, higher daily doses for these drugs have been recommended for CS [22,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Over the last 2 decades clinical results from treatment of nearly 2000 patients have been published (see Lenning 1992 for references). However, randomised trials have not revealed any difference in response rate of statistical significance (Bonneterre et al 1985;Bruning et al 1989;Robustelli della Cuna 1991;Strocchi et al 1991). Overall data from the literature suggest response rates of about 20, 25 and 30% amo~g unselected patients treated with 250, 500 or 1000 mg/ day, respectively (Lenning 1992).…”
Section: Confidence Intervals May Predict Optimal Drug Dose Ratiosmentioning
confidence: 99%